Pengaruh Service Excellence dan E-Marketing terhadap Keputusan Pembelian Persewaan Alat Pesta Barokah Jaya di Sidoarjo - Hanafi, M. Iqsan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Several factors, such as service quality and e-marketing, can influence purchasing decisions. This study examines the purchasing decisions of Barokah Jaya Sidoarjo. This study uses a descriptive quantitative approach. This study involved 99 customers of Barokah Jaya Sidoarjo from June to December 2023. However, the sample used consisted of 99 people who answered. The saturated sample method was used for sampling. Data collection was conducted through Google Form surveys featuring a range of statements rated on a Likert scale. The gathered data underwent several tests, including validity, reliability, normality, multicollinearity, heteroscedasticity tests, multiple linear regression analysis, and t-tests for individual significance. The findings indicate that service excellence has a significant influence on purchasing decisions for Barokah Jaya Sidoarjo and e-maketing has a significant influence on purchasing decisions.